Medien der Sorge, Techniken des Selbst Praktiken des Über-sich-selbst-Schreibens bei Schlingensief und Jelinek - Degeling, Jasmin (Büchner-Verlag, 2021)
Can art heal? Jasmin Degeling pursues this question via a redefinition of Michel Foucault's concepts of the technologies of the self as well as of care of the self through the lenses of media studies. For that purpose she describes and analyzes the media and aesthetics of Christoph Schlingensief and Elfriede Jelinek as aesthetic therapeutics. The example of the later works of theater, film, and action artist Christoph Schlingensief traces the modern political and aesthetic history of art as a medium of therapeutics, while Elfriede Jelinek's monumental online novel »Neid (Mein Abfall von allem) - Ein Privatroman« experiments with literary writing in virtual spaces and designs an autobiographical novel that rejects any form of literary subject constitution in a feminist way. The study brings contemporary media of care into view as exercises in healing, health, and survival, and connects them to an archaeology of the aesthetic and media history of modern concepts of health and healing.